Melanin-hydroxypropyl chitosan / hyaluronic acid-diamino polyethylene glycol composite hydrogel as well as preparation method and application thereof

By using melanin-hydroxypropyl chitosan/hyaluronic acid-bisamino polyethylene glycol composite hydrogel, the problems of insufficient adhesion and secondary damage in chronic wound repair were solved, and the effects of stabilizing adhesion, antioxidant and promoting cell growth were achieved.

CN119868634AActive Publication Date: 2025-04-25OCEAN UNIV OF CHINA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510070149.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-25
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

Existing hydrogel dressings have problems with insufficient adhesion and secondary damage to the wound and surrounding skin during peeling.

Method used

Melanin-hydroxypropyl chitosan/hyaluronic acid-bisamino polyethylene glycol (M-HPCS/HA-PEG) composite hydrogel was used to modify chitosan and graft inomelanin through etherification reaction and amide reaction to form a hydrogel with good adhesion and biocompatible.

Benefits of technology

The stable adhesion of the hydrogel to the skin is achieved, which avoids secondary damage to the wound and surrounding skin during the peeling process, enhances the toughness and photothermal properties of the hydrogel, and has antioxidant properties and the ability to promote cell growth.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119868634A_ABST
    Figure CN119868634A_ABST
Patent Text Reader

Abstract

The invention discloses melanin-hydroxypropyl chitosan / hyaluronic acid-diamino polyethylene glycol composite hydrogel as well as a preparation method and application of the melanin-hydroxypropyl chitosan / hyaluronic acid-diamino polyethylene glycol composite hydrogel. The preparation method comprises the following steps: firstly, improving the properties of CS, HA and melanin, grafting the melanin to HPCS to prepare M-HPCS to improve the solubility of the M-HPCS, then mixing the M-HPCS and HA-PEG to form composite hydrogel, and adding soluble metal ions. The two kinds of composite hydrogel prepared by the invention are relatively high in internal network crosslinking degree and relatively good in toughness; the material has good photo-thermal performance and can be used for photo-thermal treatment of wound repair; the oxidation resistance is high, and the good free radical scavenging capacity is achieved. The hydrogel has no cytotoxicity and has good biocompatibility; the cell growth promoting capability is good; the generation of new blood vessels can be promoted. Practical verification shows that the composite hydrogel prepared by the invention can promote wound healing of wounds by promoting generation of new blood vessels.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrogel preparation, and specifically relates to a melanin-hydroxypropyl chitosan / hyaluronic acid-bisamino polyethylene glycol composite hydrogel and a preparation method and application thereof. Background Art

[0002] A variety of dressings (including films, semipermeable foams, hydrocolloids and hydrogels) have been studied for the treatment of chronic wounds. Among them, hydrogels have broad application prospects in wound repair due to their excellent structural and functional properties. In recent decades of research, natural polymers such as chitosan, hyaluronic acid, sodium alginate and glucose have been widely used in the preparation of hydrogel dressings.

[0003] At present, the research on hydrogel dressings is still in the extensive research stage. The present invention conducts research in order to design a chronic wound hydrogel dressing with good performance. Summary of the invention

[0004] The present invention aims to provide a melanin-hydroxypropyl chitosan (M-HPCS) / hyaluronic acid-bisamino polyethylene glycol (HA-PEG) hydrogel, and also provides a preparation method and application of the composite hydrogel to make up for the deficiencies of the prior art.

[0005] To achieve the above object, the present invention is achieved through the following technical solutions:

[0006] A melanin-hydroxypropyl chitosan / hyaluronic acid-bisamino polyethylene glycol (M-HPCS / HA-PEG) composite hydrogel is prepared by mixing hydroxypropyl chitosan grafted with melanin and hyaluronic acid-bisamino polyethylene glycol.

[0007] Furthermore, the preparation method of the composite hydrogel comprises the following steps:

[0008] (1) Hydrophilic modification of chitosan was performed by etherification reaction to obtain hydroxypropyl chitosan, and then melanin was grafted onto HPCS by amide reaction to prepare M-HPCS; HA-PEG was prepared by amide reaction;

[0009] (2) preparing an M-HPCS solution and a HA-PEG solution, and then mixing the M-HPCS solution and the HA-PEG solution evenly and placing them in a water bath to obtain a composite hydrogel.

[0010] Furthermore, in the step (2), the prepared M-HPCS and HA-PEG are dissolved in deionized water to prepare solutions with concentrations of 7% and 4% (w / v), respectively; the M-HPCS solution: HA-PEG solution is 3-7: 7-3 (v / v).

[0011] Furthermore, the M-HPCS solution: HA-PEG solution is 7:3 (v / v); the water bath temperature is 45°C-60°C, preferably 60°C water bath treatment for 30 minutes.

[0012] A M-HPCS / HA-PEG / soluble metal ion composite hydrogel. The composite hydrogel is prepared by adding a soluble metal ion solution into a hydroxypropyl chitosan solution grafted with melanin and a hyaluronic acid-bisamino polyethylene glycol solution while stirring and mixing.

[0013] The metal ion can be a magnesium ion, that is, a M-HPCS / HA-PEG+Mg 2+ The composite hydrogel is prepared by mixing a hydroxypropyl chitosan solution grafted with melanin and a hyaluronic acid-bisamino polyethylene glycol solution while adding Mg 2+ Made of solution.

[0014] Furthermore, the preparation method of the M-HPCS / HA-PEG / soluble metal ion composite hydrogel comprises the following steps:

[0015] (1) Hydrophilic modification of chitosan was performed by etherification reaction to obtain hydroxypropyl chitosan, and then melanin was grafted onto HPCS by amide reaction to prepare M-HPCS; HA-PEG was prepared by amide reaction;

[0016] (2) preparing an M-HPCS solution and a HA-PEG solution, then mixing the M-HPCS solution and the HA-PEG solution evenly, adding a soluble metal ion solution dropwise while mixing, and placing the mixture in a water bath for a certain period of time to obtain the composite hydrogel.

[0017] Furthermore, in the step (2), the prepared M-HPCS and HA-PEG are dissolved in deionized water to prepare solutions with concentrations of 7% and 4% (w / v), respectively; the M-HPCS solution: HA-PEG solution is 3-7: 7-3 (v / v).

[0018] Furthermore, the ratio of the M-HPCS solution to the HA-PEG solution is 3:7 (v / v); the concentration of the added soluble metal ion solution is 4% (w / v), and the added volume percentage is 5%.

[0019] The M-HPCS / HA-PEG composite hydrogel or the M-HPCS / HA-PEG / soluble metal ion composite hydrogel is used in preparing products for resisting oxidation, promoting cell growth and promoting new blood vessel formation.

[0020] The M-HPCS / HA-PEG composite hydrogel or the M-HPCS / HA-PEG / soluble metal ion composite hydrogel is used in preparing products with photothermal performance.

[0021] The M-HPCS / HA-PEG composite hydrogel or the M-HPCS / HA-PEG / soluble metal ion composite hydrogel is used in preparing skin wound healing products, especially in preparing skin wound healing products for diabetic patients.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The present invention first improves the properties of CS, HA and melanin, and hydrophilically modifies chitosan through etherification reaction; prepares M-HPCS by grafting melanin onto HPCS through amide reaction to improve its solubility; prepares HA-PEG through amide reaction to improve its mechanical properties and provide a large number of amino groups for the hydrogel network. Then, M-HPCS and HA-PEG are mixed to form a composite hydrogel, and soluble metal ions can be added.

[0024] The adhesion of the two composite hydrogels prepared by the present invention is suitable for wound repair. They can not only stably adhere to the skin, but also avoid secondary damage to the wound and surrounding skin during the peeling process; the hydrogel has a strong degree of internal network cross-linking and better toughness; and has good photothermal performance, which can be used for photothermal therapy of wound repair; it has strong antioxidant properties and good free radical scavenging ability. The hydrogel is non-cytotoxic and has good biocompatibility; it has good ability to promote cell growth; and it can promote the formation of new blood vessels. The experimental results show that the composite hydrogels prepared by the present invention can promote wound healing by promoting the formation of new blood vessels. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 (I) Infrared spectra of melanin (A), chitosan, hydroxypropyl chitosan, melanin-hydroxypropyl chitosan (B), hyaluronic acid and hyaluronic acid-bisamino polyethylene glycol (C); UV-visible spectrum of melanin (D); NMR spectra of hydroxypropyl chitosan, melanin-hydroxypropyl chitosan (E), hyaluronic acid and hyaluronic acid-bisamino polyethylene glycol (F); (II) SEM (A) and TEM (B) images of melanin; (III) SEM (A) and TEM (B) images of melanin-hydroxypropyl chitosan; (IV) Particle size distribution (A) and potential distribution (C) of melanin; Particle size distribution (B) and potential distribution (D) of melanin-hydroxypropyl chitosan.

[0026] Figure 2The gelation pictures of M-HPCS / HA-PEG hydrogel (A); M-HPCS / HA-PEG (B) and M-HPCS / HA-PEG+Mg 2+ (C) Schematic diagram of the hydrogel gelation network.

[0027] Figure 3 The scanning electron micrograph (A), porosity (B) and pore size (C) of M-HPCS / HA-PEG hydrogels. 2+ Scanning electron microscopy images of the hydrogels (D, porosity (E) and pore size (F) (*p<0.05, **p<0.01, ***p<0.001).

[0028] Figure 4 are photos of M-HPCS / HA-PEG hydrogels adhered to different substrates.

[0029] Figure 5 Schematic diagram of hydrogel adhesion (A); adhesion strength of M-HPCS / HA-PEG (B) and M-HPCS / HA-PEG+Mg2+ (C) (*p<0.05, **p<0.01, ***p<0.001).

[0030] Figure 6 M-HPCS / HA-PEG and M-HPCS / HA-PEG+Mg 2+ Temperature scan of hydrogel modulus.

[0031] Figure 7 M-HPCS / HA-PEG and M-HPCS / HA-PEG+Mg 2+ Rheological properties of hydrogels. Frequency scan (A) and strain scan (B) of the modulus of M-HPCS / HA-PEG hydrogels; M-HPCS / HA-PEG+Mg 2+ Frequency sweep (C) and strain sweep (D) of hydrogel modulus.

[0032] Figure 8 M-HPCS / HA-PEG hydrogel (A) and M-HPCS / HA-PEG+Mg 2+ Swelling ratio of hydrogel (B); M-HPCS / HA-PEG and M-HPCS / HA-PEG+Mg 2+ Photothermal properties of hydrogels: Temperature rise curves of M-HPCS / HA-PEG hydrogels at different powers (C). M-HPCS / HA-PEG hydrogels at 1 W / cm 2 Temperature rise curve (D) and thermal imaging (E) under different powers; M-HPCS / HA-PEG+Mg 2+Heating curve of hydrogel (F), M-HPCS / HA-PEG+Mg 2+ Hydrogel at 1W / cm 2 Temperature rise curve (G) and thermal imaging (H) under power; M-HPCS / HA-PEG (I) and M-HPCS / HA-PEG+Mg 2+ (J) Photothermal stability of hydrogels.

[0033] Fig. 9 DPPH scavenging ability (A) and ABTS scavenging ability (B) of M-HPCS / HA-PEG+Mg 2+ DPPH scavenging ability (C) and ABTS scavenging ability (D) of hydrogel.

[0034] Fig.10 Different concentrations of M-HPCS 7 / HA-PEG 3 Relative proliferation rates of L929 cells (A) and HUVECs cells (B) after treatment with hydrogel extract at 24h and 48h.

[0035] Fig.11 Different concentrations of M-HPCS 7 / HA-PEG 3 Cell growth status of L929 cells and HUVECs cells after treatment with hydrogel extract at 24h and 48h (200×; Bar=200μm).

[0036] Fig.12 Different concentrations of M-HPCS 3 / HA-PEG 7 +Mg 2+ Relative proliferation rates of L929 cells (A) and HUVECs cells (B) after treatment with hydrogel extract at 24h and 48h.

[0037] Fig.13 Different concentrations of M-HPCS 3 / HA-PEG 7 +Mg 2+ Cell growth status of L929 cells and HUVECs cells after treatment with hydrogel extract at 24h and 48h (Bar = 200μm)

[0038] Fig.14 This is the growth status of L929 cells after co-culture with different hydrogel extracts for 1, 3, 5, and 7 days.

[0039] Fig.15The migration of HUVEC cells after co-culture with hydrogel extract for 0, 12, 24, and 36 hours. n = 5, compared with the control group, *p < 0.05, **p < 0.01, ***p < 0.001).

[0040] Fig.16 The migration of L929 cells after co-culture with hydrogel extract for 0, 12, 24, and 36 hours (n=5, compared with the control group, *p<0.05, **p<0.01, ***p<0.001).

[0041] Fig.17 Figure 1 shows the angiogenesis of HUVEC cells after co-culture with hydrogel extract for 2, 4, 6, and 8 hours (A), (B) vascular node statistics at 8 hours, and (C) tubular number statistics at 8 hours. (*p<0.05, **p<0.01, ***p<0.001).

[0042] Fig.18 The antioxidant effect of hydrogel at the cellular level. (A) Different concentrations of H 2 O 2 Effect of solution on the viability of L929 cells; (B) Effect of hydrogel on H 2 O 2 (C) DCFH-DA fluorescence staining was used to evaluate the ROS scavenging ability of the hydrogel (*p<0.05, **p<0.01, ***p<0.001).

[0043] Fig.19 M-HPCS 7 / HA-PEG 3 Hydrogel and M-HPCS 3 / HA-PEG 7 +Mg 2+ Hydrogels for healing of diabetic skin burn wounds. Photos of wound healing in different treatment groups at 0, 7, 14, 21 and 28 days. Schematic diagram of diabetic skin wound treatment and photos of wound healing.

[0044] Fig. 20 The healing rate of M-HPCS7 / HA-PEG3 hydrogel and M-HPCS3 / HA-PEG7+Mg2+ hydrogel for diabetic skin burns. The wound healing rate of different treatment groups at 0, 7, 14, 21, and 28 days was statistically analyzed. (Compared with the control group, *p<0.05, **p<0.01, ***p<0.001).

[0045] Fig.21 M-HPCS at different powers 7 / HA-PEG 3Hydrogel (A) and M-HPCS 3 / HA-PEG 7 +Mg 2+ Photothermal heating of hydrogel (B) at the wound site of rats and at 1.5W / cm 2 Thermal image at power (C).

[0046] Fig. 22 These are the hematoxylin-eosin (H&E) staining images of the wound sites of diabetic skin burn wounds in different treatment groups 0, 7, 14, 21, and 28 days after treatment.

[0047] Fig.23 These are Masson staining images of the wound sites of diabetic skin burn wounds in different treatment groups 0, 7, 14, 21, and 28 days after treatment.

[0048] Fig.24 It is M-HPCS / HA-PEG hydrogel and M-HPCS / HA-PEG+Mg 2+ In vivo anti-inflammatory ability of hydrogels. Wound tissues were immunofluorescently stained for iNOS (red) and cell nuclei (DAPI, blue) on day 7 after treatment of diabetic skin wounds in different treatment groups.

[0049] Fig.25 It is M-HPCS / HA-PEG hydrogel and M-HPCS / HA-PEG+Mg 2+ In vivo anti-inflammatory ability of hydrogels. Wound tissues were immunofluorescently stained for CD206 (green) and cell nuclei (DAPI, blue) on day 7 after treatment of diabetic skin wounds in different treatment groups.

[0050] Fig.26 It is M-HPCS / HA-PEG hydrogel and M-HPCS / HA-PEG+Mg 2+ Immunofluorescence staining of ɑ-SMA (green) and cell nuclei (DAPI, blue) was performed on the wound tissues of diabetic skin wounds treated with different treatment groups on the 7th day.

[0051] Fig. 27 It is M-HPCS / HA-PEG hydrogel and M-HPCS / HA-PEG+Mg 2+ Immunofluorescence staining of CD31 (red) and cell nuclei (DAPI, blue) was performed on wound tissues of diabetic skin wounds treated with different treatment groups on day 7. DETAILED DESCRIPTION

[0052] The technical solution of the present invention is further described below in conjunction with embodiments.

[0053] The following reagents were required for the experiment: melanin extracted from the needleless squid, chitosan (Mw: 40 kDa, DD: 95.43%), commercially available reagents: hyaluronic acid (HA), carbodiimide hydrochloride (EDC·HCL) and N-hydroxysuccinimide (NHS), isopropanol, propylene oxide and magnesium chloride hexahydrate (MgCl 2 6H 2 O), HUVEC human umbilical vein endothelial cells and L929 mouse fibroblasts, DMEM high glucose medium, Calcein-AM / PI kit and DCFH-DA fluorescent dye, MTT, sodium pentobarbital, paraformaldehyde, potassium dihydrogen phosphate, disodium hydrogen phosphate, citric acid and sodium citrate, streptozotocin (STZ), hemostatic guaiac gauze (positive control), hematoxylin and eosin staining kit and modified Masson trichrome staining kit, immunohistofluorescence kit, xylene and neutral gum.

[0054] Example 1: In this example, melanin, hydroxypropyl chitosan (HPCS), melanin-hydroxypropyl chitosan (M-HPCS) and hyaluronic acid-bisamino polyethylene glycol (HA-PEG) were prepared.

[0055] 1. Preparation of melanin: Take cuttlefish ink, wash with anhydrous ethanol, and obtain a primary extract of cuttlefish ink melanin; soak the primary extract in deionized water, and after 24 hours, centrifuge to obtain a precipitate, place the precipitate in deionized water with a mass of 50 times, adjust the pH to 10.5, add 1.5wt% alkaline protease, inactivate the enzyme, wash the precipitate with deionized water to neutrality, freeze-dry, obtain purified melanin, and store it in a refrigerator at 4°C.

[0056] 2. Preparation of HPCS: 3 g of chitosan was placed in 20 mL of NaOH solution, stirred to dissolve, and frozen at -40 °C overnight. After thawing, the chitosan was filtered to remove excess alkali solution. After adding chitosan to 40 mL of isopropanol and stirring at room temperature for 30 min, propylene oxide was added dropwise and stirred in a 50 °C water bath. The reaction was terminated after 24 h. The reaction product was filtered to remove excess reagents, and washed with anhydrous ethanol several times after filtration, and then dissolved with deionized water, and 1 mol / L hydrochloric acid solution was added dropwise to adjust the pH to neutral. HPCS was obtained after dialysis and freeze-drying.

[0057] 3. Preparation of M-HPCS: Accurately weigh a certain amount of hydroxypropyl chitosan and dissolve it in Tris buffer (0.01g / mL) for later use. Add 0.66g of melanin to 33mL of Tris buffer (0.02g / mL), ultrasonically disperse for 20min, then add 0.31g of EDC and 0.23g of NHS, stir at room temperature for 2h, then add the above fully dissolved hydroxypropyl chitosan solution dropwise, and stir for 12h. After the reaction is completed, dialyze in deionized water for 48h to remove impurities, and freeze-dry to obtain.

[0058] 4. Preparation of HA-PEG: Dissolve HA in ultrapure water (0.01 g / mL), add 0.31 g EDC and 0.23 g NHS to activate the carboxyl group, stir at room temperature for 1 hour, add NH2-PEG-NH2 to the above solution, stir at room temperature for 12 hours, after the reaction is completed, dialyze in deionized water for 48 hours to remove impurities, and lyophilize to obtain.

[0059] The properties of the melanin, HPCS, M-HPCS and HA-PEG prepared above were characterized:

[0060] 1. The infrared absorption spectra of melanin, CS, HPCS, M-HPCS, HA and HA-PEG were collected using a Fourier transform infrared spectrometer, and the nuclear magnetic resonance hydrogen spectra of HPCS, M-HPCS, HA and HA-PEG were obtained by nuclear magnetic resonance characterization, and the chemical structures of HPCS, M-HPCS and HA-PEG were studied.

[0061] The chemical structure of melanin was analyzed by measuring the absorbance of the melanin solution in the wavelength range of 200-600nm using a UV-visible spectrophotometer.

[0062] Melanin and M-HPCS were dissolved in deionized water to prepare a solution. The particle size distribution, Zeta potential and polydispersity index (PDI) were measured using a Malvern laser particle size analyzer, and the morphology was observed using a scanning electron microscope and a transmission electron microscope.

[0063] Table 1

[0064]

[0065] The substitution degree of propylene oxide and melanin in melanin-hydroxypropyl chitosan and the substitution degree of PEG in HA-PEG were determined by elemental analysis. After freeze-drying CS, HPCS, M-HPCS and HA-PEG, a certain amount was taken and tested in an elemental analyzer to test the content of C, H and N in each substance. The content of IPA, Melanin, NH 2 -PEG-NH 2The degree of substitution is calculated as follows:

[0066]

[0067]

[0068] Where (C / N) HPCS is the carbon-nitrogen ratio of HPCS, DA is the degree of deacetylation of chitosan, DS IPA is the degree of substitution of propylene oxide, (C / N) M-HPCS is the carbon-nitrogen ratio of M-HPCS, DS ME is the degree of substitution of melanin, (C / N) HA-PEG is the carbon-nitrogen ratio of HA-PEG, DS PEG is the degree of substitution of PEG. By simplifying formulas 2-1, 2-2 and 2-3, the degrees of substitution can be obtained.

[0069] Result analysis:

[0070] 1. Preparation and characterization of melanin, HPCS, M-HPCS and HA-PEG

[0071] Figure 1 In the Fourier infrared spectrum of melanin, 1330cm -1 The absorption peak at 1585cm is caused by the deformation of phenolic hydroxyl group OH and CO stretching; -1 The characteristic peak at 3408cm is attributed to the stretching vibration of C=C on the aromatic ring; -1 The strong and broad bands at 1024cm in the infrared spectrum of chitosan may be attributed to the stretching vibration of OH and NH. These absorption peaks are representative characteristic peaks of melanin. The results show that melanin extraction is successful. -1 ,1080cm -1 ,1155cm -1 and 891cm -1 The characteristic peak shows its polysaccharide structure, 1155cm -1 The characteristic peak at 1155cm is caused by the stretching vibration of CO at the C6 position of chitosan. -1 The characteristic peak at 2973 cm -1 -CH 3 Stretching vibration peak, 1463 cm -1 -CH appears 3 The bending vibration peaks indicate the introduction of hydroxypropyl groups, while the peaks at 1068 cm -1 The characteristic peaks at 1595 cm -1 The absorption peak of -NH2 A small amount of hydroxypropyl groups were also introduced, indicating that hydroxypropyl chitosan was successfully synthesized.

[0072] The infrared spectrum of melanin-hydroxypropyl chitosan shows 3417 cm -1 ,1523cm -1 ,1646cm -1 The absorption peak at 1378 cm is considered to be the representative characteristic of melanin. -1 The absorption peak at 1523 cm is attributed to the OH deformation and CO stretching of the phenolic hydroxyl group; -1 The characteristic peak at 1646cm is caused by the stretching vibration of C=C on the aromatic ring; -1 The stretching vibration of C=O on the amide bond is 3417cm -1 The strong and broad bands were caused by the stretching vibrations of OH and NH, indicating that melanin was successfully grafted onto hydroxypropyl chitosan.

[0073] In the infrared spectrum of hyaluronic acid, 1323 cm -1 The characteristic peak at 1375cm is caused by the bending vibration of -OH. -1 and 1406cm -1 The characteristic peak at 1563cm is caused by CH bending vibration. -1 The characteristic peak at 1618cm is caused by NH stretching vibration. -1 The characteristic peak at 2923cm is caused by C=O stretching vibration. -1 The characteristic peak at is attributed to -CH 2 and -CH 3 Stretching vibration peak. In the infrared spectrum of HA-PEG, 1738cm -1 The characteristic peak at 1480 cm-1 is attributed to the stretching vibration peak of C=O in the amide bond. -1 The characteristic peak at is due to NH 2 -PEG-NH 2 This indicates that HA-PEG was successfully synthesized.

[0074] like Figure 1 -(Ⅱ), in hydroxypropyl chitosan 1 In the H-NMR spectrum, the signal peaks at 0.97ppm and 1.08ppm represent the C9 proton absorption peaks, indicating the hydroxypropylation of chitosan; the signal peaks at 3.20ppm-3.84ppm represent the C3-C8 proton absorption peaks, the signal peak at 3.01ppm represents the C2 proton absorption peak, and the signal peak at 4.76ppm reflects the C1 proton peak. 1 H-NMR spectrum of melanin-hydroxypropyl chitosan 1In the H-NMR spectrum, H 3.49ppm, δ H A new chemical shift appeared at 2.48-2.69 ppm, which once again proved that HPCS and M-HPCS were successfully synthesized.

[0075] In HA and HA-PEG 1 In H-NMR spectrum, the signal peak at a displacement of about 8 ppm is the hydrogen on the NH of the amide bond, and the proton peak b at a displacement of about 1.6 ppm is the NH of PEG. 2 The peak e at about 3.5ppm is the hydrogen ion of the methylene group adjacent to oxygen in the PEG structure, while the peaks c and d between 2.5-3.0ppm belong to the hydrogen ion of the methylene group connected to the amino group in the PEG structure. The results show that PEG was successfully grafted onto HA.

[0076] The UV-visible spectrum of melanin is shown in Figure 1 -(Ⅱ)-D shows that there is a maximum absorption peak at 200nm, which is attributed to the benzene ring, and the absorbance in the visible light region gradually decreases with the increase of wavelength, which is caused by the conjugated structure in the melanin structure.

[0077] Figure 1 -(III) is the scanning electron microscope and transmission electron microscope images of melanin. It can be clearly seen from the images that the melanin nanoparticles are uniform spherical or ellipsoidal, with clear edges, easy to agglomerate, and the particle size is about 200nm. Figure 1 -(Ⅳ) is the scanning electron microscope (A) and transmission electron microscope (B) morphology of M-HPCS. From Figure A, it can be observed that M-HPCS is uniformly spherical or ellipsoidal, with an average particle size of about 200nm and uniform distribution, which is consistent with the DLS test results. The results show that melanin can still self-assemble into nanospheres after grafting on hydroxypropyl chitosan through amide reaction, and the transmission electron microscope image in Figure B clearly shows that M-HPCS has an obvious core-shell structure, indicating that melanin is successfully grafted on hydroxypropyl chitosan.

[0078] like Figure 1 -(V) shows that the average particle size of melanin is 164±3.95nm, and PDI=0.064±0.007, indicating that the prepared melanin nanoparticles have a relatively uniform particle size and good dispersibility. Figure 2-8 The Zeta potential of melanin is -25.3±0.36 mV. The average particle size of M-HPCS is 396±0.24 nm, and PDI is 0.18±0.021, indicating that the prepared M-HPCS is a nanoparticle, and the particle size of M-HPCS is relatively uniform and has good dispersibility. Figure 2-14This is the Zeta potential detection result of M-HPCS. The Zeta potential of M-HPCS is +10.06±1.12 mV.

[0079] The C, N and H element contents of CS, HPCS, M-HPCS and HA-PEG were measured by elemental analysis as shown in Table 1. The C / N was calculated. According to the above formulas 2-1, 2-2 and 2-3, the deacetylation degree was 80.56%, the grafting degree of hydroxypropyl was 116%, and the substitution degree of melanin was 87.54%, indicating that melanin was successfully grafted onto HPCS. The substitution degree of PEG was 45.23%. The results showed that M-HPCS and HA-PEG were successfully synthesized with a high grafting rate.

[0080] Example 2: Preparation of M-HPCS / HA-PEG and M-HPCS / HA-PEG+Mg 2+ Composite hydrogel

[0081] 1. Preparation of M-HPCS / HA-PEG composite hydrogel: Determination of hydrogel gelation time by vial inversion method. Specific method: Dissolve the prepared M-HPCS and HA-PEG in deionized water to prepare solutions with concentrations of 7% and 4% (w / v), respectively. After fully stirring, mix the M-HPCS solution and HA-PEG solution in glass bottles according to different ratios (1:9; 3:7; 1:1; 7:3; 9:1), immerse in water baths at different temperatures at the initial temperature, test the gelation time of the hydrogel under each temperature condition, and invert the glass bottle after a certain time in the water bath. If no solution flows down the wall within 1 minute, it is considered to have formed a hydrogel, and the time is recorded.

[0082] 2. Preparation of M-HPCS / HA-PEG+Mg 2+ Hydrogel

[0083] Weigh 0.4066 g of magnesium chloride and dissolve it in 10 mL of deionized water to prepare a 4% (w / v) magnesium chloride solution. Take 0.1 mL of the magnesium chloride solution and drop it into 2 mL of the mixed solution to prepare a hydrogel containing a magnesium ion concentration of 10 mM.

[0084] Based on the above experiments, the prepared M-HPCS and HA-PEG were dissolved in deionized water to prepare solutions with concentrations of 7% and 4% (w / v), respectively. After being fully stirred, the M-HPCS solution and the HA-PEG solution were mixed in a glass bottle in different ratios (3:7; 1:1; 7:3), and Mg was added dropwise while stirring. 2+ Solution (ratio: 5%, v / v), 2 mL of each ratio was prepared, and the mixed M-HPCS / HA-PEG+Mg 2+The solution is immersed in water baths at different temperatures at the initial temperature, and the gelation time of the hydrogel is tested under each temperature condition, that is, it is placed in a water bath for a certain period of time, and then the glass bottle is inverted after being taken out. If no solution flows down the wall within 1 minute, it is considered to have formed a hydrogel, and the time is recorded.

[0085] Since the melanin structural unit monomer has a large number of phenolic hydroxyl groups, it can produce a strong chelating effect with metal ions. Therefore, it is inferred from the mechanism of action that various metal ions (Fe 2+ , Cu 2+ , Ca 2+ , Fe 2+ etc.) can further cross-link with the melanin-based hydrogel (M-HPCS3 / HA-PEG7), so the technical protection of the method for constructing the complex metal ion hydrogel in the present invention is not limited to Mg 2+ , other metal ions should also be covered. In this embodiment, Mg 2+ Take this as an example to illustrate.

[0086] 1. M-HPCS / HA-PEG and M-HPCS / HA-PEG+Mg 2+ Microstructure of hydrogel

[0087] Different ratios of M-HPCS / HA-PEG and M-HPCS / HA-PEG+Mg 2+ After the hydrogel is formed, it is placed in a -20℃ refrigerator and frozen overnight, and then freeze-dried in vacuo to obtain a xerogel. The xerogel is cut to obtain a cross section, and the microstructure inside the hydrogel is observed under a scanning electron microscope after treatment. 2+ The hydrogel was measured from 5 different regions, with at least 5 pore sizes selected from each region.

[0088] 2. M-HPCS / HA-PEG and M-HPCS / HA-PEG+Mg 2+ Adhesion of hydrogel

[0089] The adhesion properties of the hydrogel were tested using a universal testing machine and a macroscopic adhesion test. The adhesion properties of the hydrogel were studied macroscopically using materials such as pig skin, polyethylene film, glass bottles, weights, and rubber through a tensile adhesion test. Fresh pig skin was soaked in alcohol to remove fat, and then soaked in PBS buffer for later use. The treated pig skin was cut into strips with a width of 2 cm and a length of 5 cm, and bonded to the hydrogel (adhesion area of ​​20 mm × 20 mm) and a certain weight was applied at room temperature to allow the hydrogel to interact with the pig skin for 1 hour. A lap shear test was performed using a universal testing machine at a constant speed of 2 mm / min (n≥5) in a tensile mode, and the maximum force N was recorded. MaxThe tensile adhesion strength of the hydrogel was determined by dividing the maximum force (N) by the adhesion area (m 2 ) was calculated, and each group of experiments was repeated 3 times.

[0090] 3. M-HPCS / HA-PEG and M-HPCS / HA-PEG+Mg 2+ Rheological properties of hydrogels

[0091] Based on the determination of the hydrogel gelation time by the vial inversion method, the solution ratio that can be gelled was screened out, and 5 mL of each mixed solution ratio was prepared. The hydrogel gelation temperature was determined using a rheometer. The specific operation was as follows: the prepared M-HPCS / HA-PEG solution was injected onto the test platform of the rheometer, the plate spacing was set to 1000 μm, the frequency was set to 1 Hz, the strain was set to 1%, the temperature was set to 25°C-70°C, 2°C / min, and the temperature corresponding to the intersection of the storage modulus and the loss modulus was the gelation temperature.

[0092] The oscillation frequency of hydrogels with different proportions was scanned to explore the structural stability of hydrogels with different proportions. The parameters of the rheometer were set as follows: scanning frequency range 0.1-100 Hz, shear strain 1%, temperature 37°C, and the change of modulus with frequency was recorded after the measurement.

[0093] Oscillating strain scanning was performed on hydrogels with different proportions to explore the reversible deformation and stability of hydrogels with different proportions. The parameter settings of the rheometer were as follows: shear strain range of 1%-100%, frequency of 1Hz, temperature of 37°C. After the measurement, the change of modulus with shear strain was recorded.

[0094] 4. M-HPCS / HA-PEG and M-HPCS / HA-PEG+Mg 2+ Swelling properties of hydrogels

[0095] The freeze-dried hydrogel was weighed and immersed in PBS buffer (pH = 7.4), and placed in a constant temperature box at 37 ° C. The samples were taken out at different time points, and the excess water on the surface of the gel was wiped with filter paper and weighed until the weight of the gel no longer changed, indicating that the gel swelling reached equilibrium. Three parallel samples were set in each group, and the changes in gel weight were recorded respectively. The average value was taken, and the swelling rate was calculated according to the formula:

[0096]

[0097] Among them, W d ——Mass of dry hydrogel, unit: g

[0098] 5. M-HPCS / HA-PEG and M-HPCS / HA-PEG+Mg 2+ Photothermal properties of hydrogels

[0099] The different volume ratios of M-HPCS / HA-PEG and M-HPCS / HA-PEG+Mg 2+ Hydrogel (1 mL) was exposed to different power densities (0.5, 0.75, 1, 1.25, 1.5 W / cm 2 ) for 10 min, and the M-HPCS / HA-PEG hydrogel was heated by near-infrared laser irradiation (808 nm, 1 W / cm 2 ,5min) and natural cooling (5min), 5 cycles to evaluate its photothermal stability. At the same time, an infrared thermal imager was used to monitor the temperature changes and capture thermal images.

[0100] 6. M-HPCS / HA-PEG and M-HPCS / HA-PEG+Mg 2+ Antioxidant properties of hydrogels

[0101] (1) DPPH scavenging ability determination

[0102] Different ratios of M-HPCS / HA-PEG and M-HPCS / HA-PEG+Mg 2+ After the hydrogel is gelled, it is freeze-dried and ground into powder. 20 mg of dry gel is weighed and added with 2 mL of DPPH working solution. After being placed on a shaker at 37 °C in the dark for 30 min, the absorbance at 515 nm is adjusted to zero with ethanol. The absorbance of hydrogels of various proportions is measured and recorded as A. 1 After the M-HPCS / HA-PEG hydrogels with different ratios were gelled, they were freeze-dried and ground into powder. 20 mg of dry gel was weighed and added to 2 mL of ethanol solution as the control group. After being placed on a shaker at 37°C in the dark for 30 minutes, the absorbance at 515 nm was adjusted to zero with ethanol. The absorbance values ​​of the hydrogels with different ratios were measured and recorded as A. 2 Measure 1 mL of ethanol and add 2 mL of DPPH working solution as the control group. Use ethanol to adjust the absorbance at 515 nm to zero. Determine the absorbance of hydrogels of various proportions in turn. Record A 0 The DPPH free radical scavenging rate was calculated according to the following formula:

[0103]

[0104] (2) ABTS scavenging ability assay

[0105] Weigh 1 mg of M-HPCS / HA-PEG and M-HPCS / HA-PEG+Mg in different ratios. 2+ The dried gel powder was dissolved in 2 mL of ABTS+ working solution and mixed thoroughly. The mixture was incubated at room temperature in the dark for 30 min, then adjusted to zero with PBS buffer at a wavelength of 734 nm. The absorbance values ​​of hydrogels of various proportions were measured in turn, and recorded as A.1 Measure 1 mL of PBS buffer and add it to 2 mL of ABTS+ working solution and mix thoroughly as the control group. After adjusting the wavelength to zero with PBS buffer at 734 nm, measure its absorbance value and record it as A. 0 The ABTS free radical scavenging rate was calculated according to the following formula:

[0106]

[0107] 7. Cytocompatibility of hydrogels

[0108] Preparation of M-HPCS / HA-PEG hydrogel extract: Preparation of M-HPCS 7 / HA-PEG 3 Hydrogel and M-HPCS 3 / HA-PEG 7 +Mg 2+ The hydrogel was freeze-dried and weighed, then placed in a centrifuge tube for irradiation sterilization, and serum-free DMEM medium was added at a ratio of 0.1 g / mL and placed in a cell culture incubator for 72 hours to obtain the M-HPCS / HA-PEG hydrogel extract. The extract was filtered twice with a 0.22 μm filter membrane, sealed, and placed at 4°C for later use.

[0109] HUVEC cells and L929 cells in the logarithmic growth phase were digested and resuspended in DMEM complete medium to dilute to 2×10 4 200 μL of cell suspension was inoculated into a 96-well plate, i.e. 4000 cells per well, and placed at 37°C, 5% CO 2 After culturing in a cell culture incubator for 24 h to allow the cells to adhere to the wall, the cell culture medium in the well plate was discarded and different concentrations of M-HPCS were added again. 7 / HA-PEG 3 and M-HPCS 3 / HA-PEG 7 +Mg 2+ Hydrogel extract (20%, 40%, 60%, 80%, 100%), while the blank group and the control group were replaced with fresh DMEM complete medium, and continued to be placed in the cell culture incubator for 24 and 48 hours, and the cell state was observed under a microscope. The MTT method was used to evaluate the effect of hydrogel on cell proliferation. After observation and photography, 20 μL of 0.5 mg / mL MTT solution was added to each well, and the hydrogel extract and MTT solution in the well plate were discarded after incubation in the incubator for 4 hours. 150 μL of DMSO solution was added to each well, and the absorbance was read using an enzyme reader. The relative cell proliferation rate was calculated according to the following formula:

[0110]

[0111] Among them, A 实验组 is the average absorbance value of the experimental group, A 空白组 is the average absorbance value of the blank control group, A 对照组 is the average absorbance value of the control group.

[0112] 8. Live / dead cell detection of hydrogels

[0113] Live / dead cell staining was used to further evaluate the effect of hydrogel on L929 cell morphology and proliferation. After digestion, the cells were resuspended in complete medium and diluted to 4 × 10 4 cells / mL, 0.5 mL of L929 cell suspension was inoculated into a 48-well plate, i.e. 2×10 4 After 24 h of culture, the cells adhered to the wall, the culture medium was discarded, and 0.5 mL of hydrogel extract was added to each well of the experimental group, and 0.5 mL of fresh complete culture medium was added to the control group. The cells were placed in a 37°C, 5% CO 2 After incubation in a cell culture incubator for 1, 3, 5, and 7 days, the original culture medium was discarded, and the cells were washed with sterile PBS buffer. 200 μL of freshly prepared cell live and dead staining working solution was added to each well. After staining at 37°C in the dark for 20 minutes, the cell staining was observed under a fluorescence microscope with the excitation wavelength set to 560 nm and the emission wavelength set to 600 nm.

[0114] 9. Cell migration experiment of hydrogel

[0115] The cell scratch method was used to study the migration-promoting ability of hydrogels. L929 cells and HUVECs cells in the logarithmic growth phase were digested and centrifuged, and then resuspended and diluted to 3×10 in DMEM culture medium containing 10% fetal bovine serum. 5 cells / mL, 1 mL was inoculated into a 24-well plate, i.e. 3×10 cells / mL per well. 5 cells, at 37°C, 5% CO 2 The cells were cultured in a cell culture incubator until the cells adhered to the wall and covered the entire bottom of the well. The old culture medium was discarded, and a 10 μL sterile pipette tip was used to scratch the well plate vertically to make cell scratches, and then washed with sterile PBS solution to clean the cell debris, and then re-added with M-HPCS 7 / HA-PEG 3 、M-HPCS 3 / HA-PEG 7 +Mg 2+ The serum-free DMEM medium was added to the extract, and the control group was added with serum-free DMEM medium and placed at 37°C, 5% CO 2The cells were cultured in a cell culture incubator and taken out after 0, 12, 24, and 36 hours, respectively, and observed and photographed under a microscope. The cell images were analyzed using Image J. The cell migration rate was calculated using the following formula:

[0116]

[0117] Among them, S 0 It is the initial wound area before cell migration, and St is the wound area after a certain period of cell migration.

[0118] 10. Hydrogel cell angiogenesis experiment

[0119] First, use a pre-cooled pipette tip to draw 50 μL of Matrigel into a 96-well plate, and then place the plate in 37°C for 30 minutes to allow Matrigel to solidify. Then, after digesting the HUVEC cells in good condition, dilute them with FBS-free DMEM high-glucose medium to 3×10 4 Cells / well were evenly inoculated on the gelled Matrigel, and 100 μL of M-HPCS / HA-PEG hydrogel extract without FBS was added to each well of the experimental group, while DMEM high-glucose medium without FBS was added to the blank control group. After inoculating the cells, the well plate was placed at 37°C and 5% CO 2 After incubation in a cell culture incubator for 2, 4, 6, and 8 hours, the formation of blood vessels was observed under an optical microscope and photographed. The vascular nodes and blood vessels of each experimental group were counted and statistically analyzed using Image J software to determine the number of new blood vessels.

[0120] 11. Antioxidant experiment of hydrogel at the cell level

[0121] (1)H 2 O 2 Establishment of L929 cell injury model

[0122] L929 cells in the logarithmic growth phase were digested and centrifuged, and then resuspended and diluted to 2×10 in DMEM culture medium containing 10% FBS. 4 cells / mL, take 200 μL and transfer to 96-well plate, i.e. 4000 cells per well, incubate at 37°C, 5% CO 2 After the cells adhered to the wall, the old culture medium was discarded and 200 μL of different concentrations of H 2 O 2 DMEM medium (H 2 O 2The concentrations were 0, 10, 25, 50, 100, 200, 400, 600, and 800 μM, and the cells were cultured at 37°C for 2 hours to stimulate the cells to produce reactive oxygen species. After the culture was completed, 20 μL of MTT detection solution was added and incubated at 37°C with 5% CO 2 After incubation for 4 h, the absorbance was measured using an enzyme-labeled instrument to detect cell viability.

[0123] (2) ROS scavenging ability assessment

[0124] In order to evaluate the protective effect of hydrogel in scavenging ROS on cells, L929 cells in the logarithmic growth phase were digested and centrifuged, resuspended and diluted to 2×10 in DMEM culture medium containing 10% FBS. 4 cells / mL, take 200 μL and transfer to 96-well plate, i.e. 4000 cells per well, incubate at 37°C, 5% CO 2 After the cells adhered to the wall, the old culture medium was discarded and 200 μL H 2 O 2 The concentration of the hydrogel extract was 500 μM, and the control group was replaced with a hydrogel extract without H 2 O 2 Fresh serum-free DMEM medium was added to the negative control group, and only H 2 O 2 After culturing at 37°C for 2 hours, 20 μL of MTT detection solution was added to the serum-free DMEM medium with a concentration of 500 μM and incubated at 37°C and 5% CO 2 After incubation for 4 h, the absorbance was measured using an enzyme-labeled instrument to detect cell viability.

[0125] (3) DCFH-DA fluorescence staining

[0126] To further evaluate the ROS scavenging ability of the hydrogel, the ROS probe DCFH-DA was used to observe cell labeling. The hydrogel was cut into 3m×3m×3m blocks (n=3), sterilized with alcohol and irradiated with ultraviolet light before use. The well-growing L929 cells were digested and centrifuged, then resuspended and diluted to 4×10 4 cells / mL, 500 μL was inoculated into a 48-well plate, i.e. 2×10 cells / mL per well. 4 cells, at 37°C, 5% CO 2 The cells were cultured in a cell culture incubator for 24 h to allow the cells to adhere to the wall. The old culture medium was discarded, and then 500 μL of 500 μM H 2 O 2 The blank group was replaced with fresh serum-free DMEM medium without H 2 O2 ; Experimental group: After adding the culture medium, the sterilized hydrogel was carefully placed in the well plate and incubated at 37°C for another 2 hours. Then the solid hydrogel was gently taken out, the old culture medium was aspirated and discarded, and the sterile PBS solution was washed, and 200 μL of 2', 7'-dichlorofluorescein diacetate (DCFH-DA) was added, and the cells were placed in a cell culture incubator and incubated in the dark for 20 minutes, and then washed with serum-free culture medium to wash away the unloaded DCFH-DA. Finally, the intracellular fluorescence was observed with a fluorescence microscope or laser confocal scanning microscope and photographed.

[0127] 12. Establishment of diabetic rat model, burn wound model and skin wound healing study

[0128] Preparation of STZ solution: Accurately weigh a certain amount of STZ powder, add citric acid buffer to prepare a 10mg / mL STZ solution, store in dark and use within 30min. After the purchased male SD rats (8-10 weeks old, 200-250g) were raised for one week, the blood glucose levels of the rats were monitored at the same time to determine that they were normal rats. After the rats adapted to the environment, they were fasted but not watered for 12h. The diabetic mouse model was induced by intraperitoneal injection of STZ solution (dose: 65mg / kg; concentration: 40mg / mL) into male SD rats. After the injection, they were fasted but not watered for 2h. The blood glucose levels of the rats were measured every 3 days. If the blood glucose concentration was above 16.7mM, the rats were considered to have diabetes, and subsequent surgery could be performed if the model was successfully established.

[0129] The diabetic SD rats were randomly divided into six groups, 25 in each group, namely, blank control group, positive control group (hemostatic guaiac gauze), M-HPCS 7 / HA-PEG 3 Hydrogel group, M-HPCS 7 / HA-PEG 3 Hydrogel+NIR group, M-HPCS 3 / HA-PEG 7 +Mg 2+ Hydrogel group, M-HPCS 3 / HA-PEG 7 +Mg 2+Hydrogel + NIR group. After anesthetizing the diabetic rats with 3% sodium pentobarbital (1mL / kg), shave the hair on the back of the rats and remove the hair with a depilatory cream. Disinfect the back with 75% alcohol. After the skin surface is dry, press the rat back skin for 15s with a constant temperature scald instrument at 80°C and 500g to establish a wound diameter of 1.6cm deep second-degree scald wound model. After carefully removing the necrotic skin on the back of the rat, apply the hydrogel dressings of each group to the wound and ensure that the wound is completely covered. The blank control group uses normal saline, and then covers the wound surface with a dressing and a bandage. Finally, wrap it with medical tape to prevent the rat from biting the wound and the hydrogel from falling off. The hydrogel dressing was changed every two days after surgery, and the wound healing was recorded by taking pictures and measuring the wound size. The wound area was measured by Image J software, and the wound healing rate was calculated as shown below:

[0130]

[0131] Where S 0 and S t They are the initial wound area on day 0 and the wound area on the specified date, respectively.

[0132] 13. In vivo photothermal conversion research

[0133] 0.2 mL of M-HPCS / HA-PEG hydrogel was applied to the burn wound of rats at different power densities (1, 1.25, 1.5 W / cm 2 ) for 5 min, and the M-HPCS / HA-PEG hydrogel was heated by near-infrared laser irradiation (808 nm, 1 W / cm 2 ,5min) and natural cooling (5min), 5 cycles to evaluate its photothermal stability. At the same time, an infrared thermal imager was used to monitor the temperature changes and capture thermal images.

[0134] 14. HE staining, Masson staining and immunofluorescence staining observation of tissue sections

[0135] On the 3rd, 7th, 14th, 21st and 28th days after treatment in different treatment groups, 5 rats were randomly selected from each group, and the skin tissues at the burn wound were cut and fixed in 4% paraformaldehyde fixative for 24 hours for subsequent staining. After fixation, the tissue blocks were rinsed with water for 12 hours, and then the tissue blocks were trimmed into regular shapes and dehydrated with 50%, 70%, 95% ethanol and anhydrous ethanol I and II for 2 hours in turn; the dehydrated tissues were soaked in xylene for 15 minutes, and then soaked in fresh xylene for 15 minutes to make the tissue transparent; finally, the tissue blocks were soaked in paraffin I, paraffin II and paraffin III for 1 hour in turn and then embedded. The embedded tissue blocks were fixed on a tissue slicer, cut into 5μm tissue sections, placed in 40℃ deionized water for expansion, and the sections were fished out with anti-shedding slides, and dried overnight. After drying at 62°C for 1-2h, the sections were dewaxed with xylene I and xylene II for 10min respectively, soaked in a xylene / anhydrous ethanol mixture (volume ratio 1:1) for 5min, and then soaked in anhydrous ethanol I and II, 95%, 85%, 70% ethanol and distilled water for 2min respectively, then stained with hematoxylin solution for 10min, rinsed with distilled water for 3min, differentiated with 1% hydrochloric acid alcohol for 1.5s, slowly rinsed with tap water for 10min, and then treated with 70%, 85%, and 95% ethanol for 2min in turn, stained with eosin solution for 1s, and soaked in 95% ethanol I, 95% ethanol II, 95% ethanol III, anhydrous ethanol I, II and III, xylene I, and xylene II for 5min respectively, and finally sealed with neutral gum, dried in a fume hood, observed under an optical microscope and photographed.

[0136] The above tissue sections were sliced ​​and Masson staining was performed according to the instructions of the kit. Finally, the sections were sealed with neutral gum and dried, and the collagen fibers of the wound surfaces of each group were observed under a microscope.

[0137] Skin tissue sections after 7 days of treatment were sliced ​​and immunofluorescently stained for CD206, iNOS, CD31, and α-SMA to determine the inflammation and angiogenesis at the wound site to evaluate M-HPCS 7 / HA-PEG 3 Hydrogel and

[0138] M-HPCS 3 / HA-PEG 7 +Mg 2+ Inflammation-modulating and angiogenic abilities of hydrogels in vivo.

[0139] Experimental results analysis:

[0140] 1. M-HPCS / HA-PEG and M-HPCS / HA-PEG+Mg 2+Hydrogel formation conditions When the M-HPCS solution is mixed with the HA-PEG solution, the phenolic hydroxyl groups in the melanin interact with the amino groups on the HA-PEG chain through non-covalent bonds, and the hyaluronic acid and chitosan also produce chain entanglement, hydrogen bonding and other interaction forces, so that the M-HPCS / HA-PEG solution forms a 3D network structure hydrogel. 2+ After that, M-HPCS chelates with the phenolic group and phenolic hydroxyl group on melanin. 3 / HA-PEG 7 +Mg 2 + The solution can also form a hydrogel with a 3D network structure.

[0141] Under certain temperature conditions, the hydrophilic-hydrophobic balance changes, and thus the solubility of the entire polymer network changes, causing a sol-gel phase transition. Figure 2 It can be seen that before being heated in a water bath, the M-HPCS / HA-PEG mixtures of various concentrations have a certain fluidity, that is, they are still in a solution state. After 30 minutes in a 60°C water bath, except for the M-HPCS / HA-PEG mixture with a volume ratio of 1:9, which still has fluidity, that is, it has not formed a hydrogel, the other M-HPCS / HA-PEG mixtures with different volume ratios are in a gel state. The results show that M-HPCS 3 / HA-PEG 7 、M-HPCS 1 / HA-PEG 1 、M-HPCS 7 / HA-PEG 3 、M-HPCS 9 / HA-PEG 1 All solutions can form hydrogels under heating conditions.

[0142] At room temperature, various concentrations of M-HPCS / HA-PEG+Mg 2+ The mixed solution was still in solution state, but after heating in a water bath, a hydrogel was formed. Table 2 shows that M-HPCS 3 / HA-PEG 7 +Mg 2+ 、M-HPCS 1 / HA-PEG 1 +Mg 2+ 、M-HPCS 7 / HA-PEG 3 +Mg 2+ The gelation temperatures of the hydrogels were 45°C, 60°C, and 60°C, respectively. 3 / HA-PEG 7 +Mg 2+The gelation temperature is significantly reduced, which is due to the 2+ The addition of M-HPCS reacts with the hydroxyphenol group of melanin, so that the mixed solution can form a stable network structure at a lower temperature. 1 / HA-PEG 1 、M-HPCS 7 / HA-PEG 3 Without adding Mg 2+ In the case of Mg 2+ When the ratio of phenolic hydroxyl group to amino group is unbalanced, part of phenolic hydroxyl group is combined with Mg 2+ Interaction occurs, however, M-HPCS 3 / HA-PEG 7 +Mg 2+ The proportion of phenolic hydroxyl groups available in the hydrogel is relatively high, so M-HPCS 3 / HA-PEG 7 +Mg 2+ The gelation temperature of the hydrogel decreased, while Mg 2+ The addition of M-HPCS 1 / HA-PEG 1 、M-HPCS 7 / HA-PEG 3 The gelation temperature of the hydrogel has little effect.

[0143] Table 2

[0144]

[0145] 2. Microstructure of M-HPCS / HA-PEG hydrogel

[0146] The pore size of the hydrogel is very important for wound healing. Figure 3 -A, the hydrogels all have porous structures, among which M-HPCS 9 / HA-PEG 1 The internal structure of the hydrogel is loose and irregular. 3 / HA-PEG 7 、M-HPCS 1 / HA-PEG 1 、M-HPCS 7 / HA-PEG 3 The hydrogels with these three ratios all showed a porous network structure with uniform void distribution. As the proportion of M-HPCS increased, the structure of the hydrogel became tighter and the pore size became smaller. 3 / HA-PEG 7 、M-HPCS 1 / HA-PEG 1 、M-HPCS 7 / HA-PEG 3 The average pore sizes of the hydrogels are 435.26 μm, 191.22 μm, and 128.04 μm, respectively. The higher the degree of cross-linking of the hydrogel, the more cross-linking points will be formed inside it, which will lead to a decrease in the porosity and pore size of the hydrogel. Compared with M-HPCS 3 / HA-PEG 7 Hydrogel, M-HPCS 1 / HA-PEG 1 、M-HPCS 7 / HA-PEG 3 These two hydrogels have lower pore sizes and porosities, can better maintain their stable structures, and have better mechanical strength.

[0147] Studies have shown that when the pore size of the hydrogel is around 125 μm, it is conducive to the migration of contractile fibroblasts and promotes wound repair. 2+ SEM images of hydrogels Figure 3 -D, M-HPCS / HA-PEG+Mg 2+ The hydrogels all have porous structures, and the pore size and porosity are obtained by measurement. 3 / HA-PEG 7 +Mg 2+ , M-HPCS 1 / HA-PEG 1 +Mg 2+ 、M-HPCS 7 / HA-PEG 3 +Mg 2+ The average pore sizes of the hydrogels are 103.44 μm, 128.04 μm, and 97.59 μm, respectively. 7 / HA-PEG 3 +Mg 2+ The hydrogel cross-linking is relatively loose and the structure is not stable enough, while M-HPCS 3 / HA-PEG 7 +Mg 2+ 、M-HPCS 1 / HA-PEG 1 +Mg 2+ The hydrogel is tightly cross-linked and has uniform pore distribution. 2+ With the addition of M-HPCS 3 / HA-PEG 7 +Mg 2+ 、M-HPCS 1 / HA-PEG 1+Mg 2+ The porosity and pore size of the hydrogel were significantly reduced, and compared with M-HPCS 1 / HA-PEG 1 +Mg 2+ Hydrogel, M-HPCS 3 / HA-PEG 7 +Mg 2+ The average pore size of the hydrogels was significantly different. 2+ The addition of makes the cross-linking of molecules in the hydrogel more compact.

[0148] 3. Adhesion of M-HPCS / HA-PEG hydrogel

[0149] like Figure 4 As shown in the figure, after the finger is bent at different angles, the hydrogel still adheres firmly to the finger and does not fall off. After the hydrogel adheres to the skin for several minutes, the hydrogel can still be completely torn off from the skin, and the skin will not be torn in the process, and no secondary damage will be caused to the tissue. The adhesion ability of the hydrogel on the pig skin is measured by a universal testing machine, as shown in the figure. Figure 5 As shown, M-HPCS 3 / HA-PEG 7 、M-HPCS 1 / HA-PEG 1 、M-HPCS 7 / HA-PEG 3 The adhesion strengths of the hydrogels were 3511.9Pa, 3942.81Pa, and 4613.39Pa, respectively. It can be seen that the addition of melanin gave the hydrogels better adhesion, and as the melanin content increased, the adhesion of the hydrogels also gradually increased. 3 / HA-PEG 7 、M-HPCS 1 / HA-PEG 1 Compared with hydrogel, M-HPCS 7 / HA-PEG 3 The hydrogel has the best adhesion, and the adhesion is suitable for wound repair.

[0150] like Figure 5 As shown, when Mg is added 2+ After, M-HPCS 3 / HA-PEG 7 +Mg 2+ 、M-HPCS 1 / HA-PEG 1 +Mg 2+The adhesion strength of the hydrogels increased, and the adhesion forces were 6701.42 and 4457.02 Pa, respectively, and M-HPCS 3 / HA-PEG 7 +Mg 2+ The adhesion of the hydrogels changed the most, which was due to the Mg 2+ The addition of Mg 2+ It forms a chelating effect with the phenolic hydroxyl groups of melanin, occupies a large number of hydroxyl groups, and reduces the degree of cross-linking of the entire network structure, which is consistent with the results of microstructure observation. 3 / HA-PEG 7 +Mg 2+ 、M-HPCS 1 / HA-PEG 1 +Mg 2+ These two hydrogels can not only adhere stably to the skin, but also avoid secondary damage to the wound and surrounding skin during the peeling process.

[0151] 4. Rheological properties of M-HPCS / HA-PEG hydrogel

[0152] like Figure 6 As shown in (A), starting from 25°C, the storage modulus G' of the three hydrogels is higher than the loss modulus G", and the change trend is the same. The difference between the storage modulus G' and the loss modulus G" increases at 62°C, 61.91°C, and 60°C, respectively, indicating that these temperatures are the gelation temperatures of the three hydrogels.

[0153] M-HPCS 3 / HA-PEG 7 +Mg 2+ 、M-HPCS 1 / HA-PEG 1 +Mg 2+ 、M-HPCS 7 / HA-PEG 3 +Mg 2+ The gelation temperature of the hydrogel was determined by Figure 6 As shown in (B), like the M-HPCS / HA-PEG hydrogel, the storage modulus G' of these three hydrogels is higher than the loss modulus G" between 25℃ and 60℃, and the change trend is the same. This is because the viscosity of the mixed M-HPCS solution and HA-PEG solution is similar to that of the hydrogel. The difference between the storage modulus G' and the loss modulus G" of these three hydrogels at 46.55℃, 59.85℃, and 61.9℃, respectively, becomes larger, indicating that these temperatures are the gelation temperatures of the three hydrogels.

[0154] from Figure 7(A) shows that within a certain frequency range, M-HPCS 3 / HA-PEG 7 、M-HPCS 1 / HA-PEG 1 、M-HPCS 7 / HA-PEG 3 The storage modulus G' of the hydrogel is higher than the loss modulus G", indicating that the M-HPCS / HA-PEG hydrogel is in a good gel state. 3 / HA-PEG 7 Hydrogel, M-HPCS 1 / HA-PEG 1 、M-HPCS 7 / HA-PEG 3 The storage modulus G' of the hydrogel is much higher than the loss modulus G", which indicates that M-HPCS 3 / HA-PEG 7 The cross-linking degree of hydrogel is low, and its network structure is more easily destroyed under certain external forces and becomes a solution state, while M-HPCS 1 / HA-PEG 1 、M-HPCS 7 / HA-PEG 3 The hydrogel has a high degree of cross-linking and a more stable hydrogel structure, which is not easily destroyed. In addition, the storage modulus G' of these three hydrogels can reach 339.48, 1120.6, and 7492.75Pa, respectively. 7 / HA-PEG 3 The G' value of the hydrogel is significantly higher than that of M-HPCS 3 / HA-PEG 7 、M-HPCS 1 / HA-PEG 1 This is because as the melanin content increases, the cross-linking density increases and the viscoelasticity of the hydrogel increases, indicating that the addition of melanin improves the density of the hydrogel network.

[0155] At the same time, the rheometer was also used to study the change in the modulus of the hydrogel with strain, and to further evaluate the stability of the hydrogel's network structure. Oscillatory strain scanning is mainly used to determine the linear viscoelastic region (LVR) of the material. LVR can reflect the structure of the hydrogel system and characterize the stability of the hydrogel. When a certain range of oscillatory strain is applied to the hydrogel, the hydrogel will undergo reversible deformation. At this time, the structure of the hydrogel is not destroyed. Once the applied force or deformation exceeds the LVR, the hydrogel will be damaged to a certain extent, and even the structure will collapse. Figure 7(B) It can be clearly seen that within the strain range of 1%-100%, M-HPCS 3 / HA-PEG 7 、M-HPCS 1 / HA-PEG 1 、M-HPCS 7 / HA-PEG 3 The storage modulus G' of the hydrogels is higher than the loss modulus G", and relative to M-HPCS 3 / HA-PEG 7 Hydrogel, M-HPCS 1 / HA-PEG 1 Hydrogel, M-HPCS 7 / HA-PEG 3 The LVR region of the hydrogel is wider.

[0156] The viscoelasticity of the hydrogel is mainly determined by its storage modulus G' and loss modulus G". When the storage modulus is greater than the loss modulus, the viscoelasticity of the hydrogel is better, and the larger the storage modulus value, the better the viscoelasticity of the hydrogel.

[0157] M-HPCS / HA-PEG+Mg 2+ The dynamic rheological results of the hydrogel showed that ( Figure 7 (C)), within a certain range, its storage modulus G' is greater than the loss modulus G", indicating that M-HPCS / HA-PEG+Mg 2+ The hydrogel is in a gel state within this range and has a certain viscoelasticity; M-HPCS 3 / HA-PEG 7 +Mg 2+ 、M-HPCS 1 / HA-PEG 1 +Mg 2+ 、M-HPCS 7 / HA-PEG 3 +Mg 2+ The storage modulus G' of the hydrogel in the oscillation frequency range of 1-100 Hz is approximately 938.7Pa, 933.23Pa, and 297.92Pa. In this range, M-HPCS 3 / HA-PEG 7 +Mg 2+ The storage modulus of the hydrogel is large, indicating that M-HPCS 3 / HA-PEG 7 +Mg 2+ The hydrogel has good mechanical properties.

[0158] from Figure 7 As can be seen in (D), when M-HPCS 3 / HA-PEG 7 +Mg 2+ 、M-HPCS 1 / HA-PEG 1 +Mg 2+ 、M-HPCS 7 / HA-PEG 3 +Mg 2+ When the strain of the hydrogel exceeds 761%, 429%, and 180%, respectively, the trend of its storage modulus G' and loss modulus G" is reversed, which indicates that when the strain strength is exceeded, the internal structure of the hydrogel has been destroyed. Compared with M-HPCS 1 / HA-PEG 1 +Mg 2+ and M-HPCS 7 / HA-PEG 3 +Mg 2+ For hydrogels, M-HPCS 3 / HA-PEG 7 +Mg 2+ The external force required to destroy the internal structure of the hydrogel was greater, indicating that M-HPCS 3 / HA-PEG 7 +Mg 2+ The internal network of the hydrogel is highly cross-linked, has better toughness, and can withstand greater deformation without being destroyed.

[0159] 5. Swelling properties of M-HPCS / HA-PEG hydrogel

[0160] like Figure 8 As shown in (A), after immersion for 24 h, M-HPCS 3 / HA-PEG 7 、M-HPCS 1 / HA-PEG 1 , M-HPCS 7 / HA-PEG 3 The swelling ratios of the hydrogels were 54.15, 35.47, and 26.94, respectively, and the M-HPCS 1 / HA-PEG 1 , M-HPCS 7 / HA-PEG 3 The swelling ratios of these two groups of hydrogels were significantly lower than that of M-HPCS. 3 / HA-PEG 7 hydrogel, and within a suitable range, indicating that M-HPCS 1 / HA-PEG 1 , M-HPCS 7 / HA-PEG 3The hydrogel can not only quickly absorb wound exudate at the skin wound site, prevent tissue fluid leakage, and maintain a moist environment for the wound tissue, but also prevent the hydrogel from swelling and falling off. This is consistent with the observation results of the microstructure. 3 / HA-PEG 7 The network pores of the hydrogel are larger, that is, the cross-linking between its molecular chains is looser, making it easier for water molecules to enter the hydrogel network. 3 / HA-PEG 7 The hydrogel has a high swelling rate and is more likely to disintegrate; while M-HPCS 1 / HA-PEG 1 , M-HPCS 7 / HA-PEG 3 The low swelling of the hydrogels is due to the benzene ring structure of melanin, which enhances the hydrophobicity of the molecular chain. On the other hand, it also reflects that the two groups of hydrogels have a higher degree of cross-linking and smaller pores. The results of the swelling performance once again prove that as the melanin content increases, the degree of cross-linking of the hydrogel becomes tighter and its performance becomes better.

[0161] The swelling ratio of the hydrogel evaluated the ability of the hydrogel to absorb wound exudate. Figure 8 (B)

[0162] M-HPCS / HA-PEG+Mg 2+ The water absorption of hydrogel within 24 hours, due to Mg 2+ The internal structure of the hydrogel became denser after immersion for 24 hours. 3 / HA-PEG 7 +Mg 2+ 、M-HPCS 1 / HA-PEG 1 +Mg 2+ 、M-HPCS 7 / HA-PEG 3 +Mg 2+ The swelling ratios of the hydrogels were 31.10, 28.03, and 21.23, respectively. The results showed that M-HPCS / HA-PEG+Mg 2+ Hydrogels have good water absorption properties.

[0163] 6. Photothermal properties of M-HPCS / HA-PEG hydrogel

[0164] Hot water baths or mild heat stimulation can promote angiogenesis, increase the vascular density of granulation tissue in skin wounds, and improve wound healing rate. Figure 8The temperature rise of M-HPCS / HA-PEG hydrogel under near-infrared light irradiation of different powers is shown in Figure 2. 2 After irradiation with near-infrared light for 10 minutes, the temperatures can rise to 41.3, 43.4, 47.9, 51.5, and 56°C, respectively. It can be seen that the M-HPCS / HA-PEG hydrogel has a high photothermal conversion efficiency, and its temperature rise shows a certain power dependence. The greater the power, the faster the heating rate of the same hydrogel, and the higher the temperature that can be reached. On this basis, 1W / cm 2 The power was used to determine the temperature rise of hydrogels with different ratios. 3 / HA-PEG 7 、M-HPCS 1 / HA-PEG 1 , M-HPCS 7 / HA-PEG 3 Under near-infrared light irradiation, the hydrogel can heat up rapidly in a short period of time, and then tend to be stable, and the maximum temperature can reach 47.9, 51.3, and 55.45°C after 10 minutes. It can be seen that melanin gives M-HPCS / HA-PEG hydrogel good photothermal properties, and with the increase of melanin content, the photothermal properties of M-HPCS / HA-PEG hydrogel are improved. 3 / HA-PEG 7 、M-HPCS 1 / HA-PEG 1 Hydrogel, M-HPCS 7 / HA-PEG 3 Hydrogels have the highest photothermal conversion efficiency. Figure 8 (H) is M-HPCS 3 / HA-PEG 7 、M-HPCS 1 / HA-PEG 1 , M-HPCS 7 / HA-PEG 3 The hydrogel was heated to 1 W / cm 2 From the temperature-rising thermal imaging diagram under the microscope, it can be seen intuitively that with the increase of time, the high-temperature spot in the area irradiated by near-infrared light becomes larger, indicating that the temperature in this area rises. M-HPCS / HA-PEG hydrogel has good photothermal properties and can be used in photothermal therapy for wound repair.

[0165] The temperature changes of M-HPCS / HA-PEG hydrogel after five consecutive near-infrared light irradiation cycles were as follows: the first highest temperature was 51°C, the second temperature was 50.2°C, the third temperature was 51°C, the fourth temperature was 51.5°C, and the fifth temperature was 51.5°C. The temperature change of M-HPCS / HA-PEG hydrogel after five irradiations was not obvious, indicating that M-HPCS / HA-PEG hydrogel has good photothermal stability.

[0166] 1 mL of hydrogel was placed in a 1.5 mL centrifuge tube and the photothermal properties of the hydrogel were measured under 808 nm NIR laser irradiation. Figure 8 It can be seen that with the increase of time, the temperature of the hydrogel rises rapidly and then tends to be stable. After 10 minutes of NIR irradiation, M-HPCS 3 / HA-PEG 7 +Mg 2+ 、M-HPCS 1 / HA-PEG 1 +Mg 2+ 、M-HPCS 7 / HA-PEG 3 +Mg 2+ The highest temperatures of the hydrogels can reach 46.17, 48.6, and 50.1 °C, respectively. The results are similar to those of the photothermal results of M-HPCS / HA-PEG hydrogels. 2+ The photothermal properties of the hydrogels are somewhat dependent on the content of melanin, and Mg 2+ The addition of M-HPCS had no effect on the photothermal properties of the hydrogel. 3 / HA-PEG 7 +Mg 2+ 、M-HPCS 1 / HA-PEG 1 +Mg 2 + 、M-HPCS 7 / HA-PEG 3 +Mg 2+ Hydrogels have good photothermal conversion capabilities.

[0167] The photothermal stability of the hydrogels was further determined, e.g. Figure 8 As shown, after 5 irradiation cycles, the M-HPCS / HA-PEG+Mg 2+ The highest temperature of the hydrogel can reach about 47.4℃, indicating that

[0168] M-HPCS / HA-PEG+Mg 2+ The hydrogel has good photothermal stability.

[0169] 7. Antioxidant activity of M-HPCS / HA-PEG hydrogel

[0170] Depend on Fig. 9 (A) shows M-HPCS 3 / HA-PEG 7 、M-HPCS 1 / HA-PEG 1 、M-HPCS 7 / HA-PEG 3 The DPPH scavenging rates of the hydrogels were 71.99%, 74.98%, and 77.16%, respectively, indicating that the M-HPCS / HA-PEG hydrogel had good antioxidant properties, and its antioxidant properties would increase with the increase of melanin content; similarly, the ABTS scavenging experiment also showed that the M-HPCS / HA-PEG hydrogel had good antioxidant properties. 3 / HA-PEG 7 、M-HPCS 1 / HA-PEG 1 、M-HPCS 7 / HA-PEG 3 The ABTS clearance rates of the hydrogels were 72.18%, 73.23%, and 74.59%, respectively, and their antioxidant properties increased with the increase of melanin content. Experiments showed that the addition of melanin enabled the M-HPCS / HA-PEG hydrogel to have stronger antioxidant properties, and with the increase of melanin content, its antioxidant properties also became stronger.

[0171] like Fig. 9 (A), M-HPCS 3 / HA-PEG 7 +Mg 2+ , M-HPCS 1 / HA-PEG 1 +Mg 2+ 、M-HPCS 7 / HA-PEG 3 +Mg 2+ The DPPH scavenging rates of the hydrogels were 84.10%, 84.13%, and 85.26%, respectively, indicating that M-HPCS / HA-PEG+Mg 2+ The hydrogel still has good antioxidant properties, and its antioxidant properties are enhanced due to the addition of magnesium ions; similarly, Fig. 9 As shown in (B), ABTS clearance experiments also showed that M-HPCS / HA-PEG+Mg 2+ The hydrogel has good antioxidant properties, M-HPCS 3 / HA-PEG 7 +Mg2+ , M-HPCS 1 / HA-PEG 1 +Mg 2+ 、M-HPCS 7 / HA-PEG 3 +Mg 2+ The ABTS scavenging rates of the hydrogels were 73.91%, 75.19%, and 76.82%, respectively. The ABTS scavenging abilities of the hydrogels were all enhanced compared with those of the M-HPCS / HA-PEG hydrogels. The results showed that the addition of magnesium ions

[0172] M-HPCS / HA-PEG+Mg 2+ The antioxidant activity of hydrogels was enhanced, M-HPCS / HA-PEG+Mg 2+ The hydrogels all have good free radical scavenging ability.

[0173] 8. Evaluation of the Cytocompatibility of Hydrogels

[0174] from Fig.10 It can be seen that the relative proliferation rate of cells after 24 and 48 hours of culture is above 85%, and the relative proliferation rate of 48 hours is higher than that of 24 hours, both above 90%. According to the cytotoxicity rating, the hydrogel extracts of various concentrations are non-toxic to cells.

[0175] At the same time, the growth state of cells was observed by optical microscopy after culturing cells with hydrogel extracts of different concentrations for 24 and 48 h, and the biocompatibility of the hydrogel was further evaluated, such as Fig.11 As shown in the figure, under co-culture with hydrogel extracts of various concentrations, the growth status of L929 cells and HUVECs cells were good. Most of the L929 cells were spindle-shaped, and most of the HUVECs cells were cobblestone-like. The cell outlines were clearly visible, and there was no obvious atrophy or death. In addition, the number of cells increased significantly after 48 hours of culture, indicating that the hydrogel had no cytotoxicity and had good biocompatibility.

[0176] The same method was used to evaluate M-HPCS 3 / HA-PEG 7 +Mg 2+ The biocompatibility of hydrogels is determined by Fig.12 It can be seen that the relative proliferation rate of L929 cells and HUVECs cells exceeded 80% after 24h or 48h of co-culture, indicating that the addition of magnesium ions was also non-toxic to the cells and M-HPCS 3 / HA-PEG 7 +Mg 2+ The hydrogel has good biocompatibility. Fig.13It can be seen that after 24h and 48h of co-culture, L929 cells and HUVECs cells can grow and proliferate normally, with good cell morphology, and the cell number is similar to that without M-HPCS. 3 / HA-PEG 7 +Mg 2+ There was no significant difference in the cells extracted from the hydrogel, and no cell necrosis or apoptosis was found.

[0177] 9. Live / dead cell analysis of hydrogels

[0178] Live / dead cell staining was used to observe the cell morphology and proliferation of L929 cells after co-culture with hydrogels. Calcein-AM and PI dyes were used to stain live cells and dead cells, respectively. That is, green fluorescent signals represent live cells, and red fluorescent signals represent dead cells. Fig.14 It can be seen that after the first day of co-culture, the number of cells in the hydrogel group was not significantly different from that in the control group. The cells all showed a plump spindle shape and no obvious red fluorescence was observed. It can also be clearly observed that compared with the first day, the number of cells after the third, fifth, and seventh days of co-culture increased significantly, the cell morphology was normal, no obvious red fluorescence representing dead cells was observed, and the number of cells in the experimental group was slightly more than that in the control group, indicating that M-HPCS 7 / HA-PEG 3 Hydrogel and M-HPCS 3 / HA-PEG 7 +Mg 2+ Hydrogels have good ability to promote cell growth.

[0179] 10. Cell migration analysis of hydrogels

[0180] like Fig.15 and 16 As shown, for the HUVEC cell group, at 24h, M-HPCS 7 / HA-PEG 3 The confluence rate of the hydrogel group reached 55.35%, and the M-HPCS 3 / HA-PEG 7 +Mg 2+ The confluence rate of the hydrogel group reached 57.55%, which was significantly different from that of the control group. At 36 hours, the confluence rate of the hydrogel group was close to 90%, almost completely confluent, while that of the control group was only 44.11%, indicating that M-HPCS 7 / HA-PEG 3 Hydrogel and M-HPCS 3 / HA-PEG 7 +Mg 2+The hydrogels have significant ability to promote HUVEC cell migration; for L929 cells, after co-culture with the hydrogel extract for 12h and 24h, the confluence rate of the hydrogel group was significantly different from that of the control group, and after 36h, the confluence of the hydrogel group was close to 50%, while the confluence rate of the control group was only 18.02%, and there was a significant difference between the hydrogel group and the control group. The results showed that compared with the control group, the hydrogel group significantly accelerated the migration speed of HUVEC cells and had a relatively good promoting effect on the migration of L929 cells, indicating that M-HPCS 7 / HA-PEG 3 Hydrogel and M-HPCS 3 / HA-PEG 7 +Mg 2+ Hydrogel can promote cell migration and accelerate wound healing during the wound healing process.

[0181] 11. Angiogenesis analysis of hydrogels

[0182] like Fig.17 As shown in the figure, compared with the blank control group, the hydrogel group showed angiogenesis after 2 hours, a small amount of angiogenesis after 4 hours, and obvious tubular structures were observed in the hydrogel group at 8 hours, indicating that new blood vessels had been generated, while the control group showed only a slight angiogenesis trend. The new blood vessels were quantified by counting the number of vascular nodes and the number of blood vessels. The results are shown in the figure. Figure 5-8 (B) and (C) show that at 8 h, in M-HPCS 7 / HA-PEG 3 In the hydrogel group, the average number of nodes and blood vessels was 48 and 78, respectively. 3 / HA-PEG 7 +Mg 2+ The average number of nodes and blood vessels in the hydrogel were 46 and 77, which were twice that of the control group, indicating that the hydrogel can promote the formation of new blood vessels.

[0183] 12. Analysis of the antioxidant capacity of hydrogel

[0184] The MTT method was used to study H 2 O 2 The degree of damage to L929 cells was determined by Fig.18 (A) It can be seen that H 2 O 2 Too high a concentration can lead to severe cell apoptosis. 2 O 2 Too low a concentration had no significant effect on cell activity, that is, at concentrations of 0, 10, 25, 50, 100, 200, and 400 μM H 2 O 2After stimulating L929 cells for 2 hours, the cell viability was still above 80%, while H 2 O 2 When the concentration was 600 and 800 μM, the cell viability was 13.42% and 9.60%, respectively. 2 O 2 The cell viability was higher at a concentration of 400 μM. 2 O 2 The cell viability was low at a concentration of 600 μM, so 500 μM H 2 O 2 The protective effect of M-HPCS / HA-PEG hydrogel on L929 cells was studied by varying the concentration of M-HPCS / HA-PEG hydrogel.

[0185] like Fig.18 As shown in (B), H 2 O 2 When the concentration was 500 μM, the cell viability of L929 cells was 67.36% after 2 hours of stimulation, while at different concentrations of M-HPCS 7 / HA-PEG 3 Under the antioxidant effect of the hydrogel extract, the cell viability of L929 cells was significantly increased, and M-HPCS 7 / HA-PEG 3 The cell viabilities of the hydrogel extract at concentrations of 20%, 40%, 60%, 80%, and 100% were 94.71%, 99.87%, 92.59%, 98.41%, and 98.41%, respectively, indicating that M-HPCS 7 / HA-PEG 3 Hydrogel for H 2 O 2 It has a protective effect on damaged cells. 2+ It can reduce the influx of calcium ions across the membrane, protect the membrane, and reduce the generation of free radicals. Therefore, M-HPCS 3 / HA-PEG 7 +Mg 2+ The cell viabilities when the hydrogel extract concentrations were 20%, 40%, 60%, 80%, and 100% were 98.15%, 107.67%, 106.35%, 105.99%, and 103.57%, respectively, indicating that M-HPCS 3 / HA-PEG 7 +Mg 2+ Hydrogel for H 2 O 2 It also has a protective effect on damaged cells, and its antioxidant effect is stronger than that of M-HPCS. 7 / HA-PEG 3 Hydrogels are strong.

[0186] from Fig.18 As can be seen from (C), without adding H 2 O 2 There was almost no obvious green fluorescence in the blank group of hydrogel, indicating that no large amount of reactive oxygen species was produced in the cells without stimulation, and the cell morphology was good. 2 O 2 In the control group, a stronger green fluorescence signal was found, indicating that H 2 O 2 It enters the cells and stimulates them to produce a large amount of ROS. Under bright field, it can be observed that the cell morphology of a large number of L929 cells has changed, shrinking and becoming round, indicating that the cells are damaged and apoptotic. Under the intervention of hydrogel, M-HPCS 7 / HA-PEG 3 、M-HPCS 3 / HA-PEG 7 +Mg 2+ Compared with the control group, the two hydrogel groups did not have strong green fluorescence, that is, no large amount of reactive oxygen species were produced in the cells, and most of the cells were still in good condition with a spindle-shaped morphology. This result is consistent with the antioxidant results, indicating that the hydrogel can intervene in H 2 O 2 It stimulates cells, regulates the level of active oxygen in cells, balances oxidation and anti-oxidation, prevents oxidative stress, and thus protects cells.

[0187] 13. Observation of wound healing

[0188] like Fig.19As shown, a deep second-degree burn was performed on the back of the rat using a burn instrument. After the burn, the wound surface immediately turned white, slightly swollen, and no body fluid exuded. On the third day after the wound was treated with different treatment methods, it can be observed that the edges of the wound surface in each group turned red. The wound surface of the control group was still white, without scabs, more swollen than just after the burn, and slightly suppurated, indicating that there was a more serious inflammation on the surface of the wound; while the positive control group had partially scabbed, without swelling, and the wound was slightly reduced; the experimental group had completely scabbed, the scab surface was flat and regular, slightly higher than normal skin, and there was no swelling, and the wound was reduced. On the 7th day, the wound of the blank group was scabbed and still swollen. It can be seen that the scab surface was significantly higher than the normal skin, and the scab surface was extremely uneven. The color was slightly yellow-green, which was different from that of the other groups, indicating that there was still severe inflammation at the wound; while the control group and the experimental group completely formed a flat and regular hard scab, without swelling, no obvious inflammation, and normal color. The scabs at the edges of the wounds in the two groups were raised. It can be observed from the figure that the wound area of ​​the experimental group was smaller than that of the control group and the positive control group, and the wound area of ​​the two NIR groups was significantly smaller than that of the two groups, indicating that NIR can promote wound healing. On the 14th day, the wound of the blank group was slightly swollen, without obvious inflammation, and the wound was slightly reduced, while the wound edges of the positive control group and the experimental group were slightly raised, the scab surface had no obvious color and texture changes, and the size of the wound was significantly smaller than that of the 7th day. On the 21st day, the wound surface of the control group was dark red, indicating that there was congestion on the epidermis, and the wound area was much larger than that of the experimental group; the scabs in the positive control group fell off, and there was also slight congestion on the surface, and the wound size was slightly smaller than that of the control group; most of the scabs in the experimental group had fallen off, and the skin surface after falling off was smooth and pink, indicating that new granulation tissue had been generated, and new hair could be observed around the wound. On the 28th day, some of the control group still had not completely shed scabs, and the wound surface had not completely healed; the wound surface of the positive control group had not completely healed, and its skin was red. The experimental group had completely healed, and some of the skin had no obvious difference from the surrounding normal tissue, and no scar was formed.

[0189] 14. Analysis of wound healing rate

[0190] like Fig. 20 As shown in the figure, on the 3rd day, the healing rates of the wounds in each group were low, with the healing rate of the control group being only 2%, while the healing rates of the other groups were around 15%; on the 7th day, the healing rate of the control group was 14.87%, while the healing rates of the hydrogel group were significantly different, and the M-HPCS 7 / HA-PEG 3 Hydrogel and M-HPCS 3 / HA-PEG 7 +Mg 2+ The healing rate of the hydrogel group was about 30%, and the healing rate of the hydrogel + NIR group was about 38%. On the 14th day, the healing rates of all groups increased significantly, with the healing rate of the control group being 40.32%, and the healing rates of the other groups ranging from 52.73% to 63.75%.7 / HA-PEG 3 Hydrogel+NIR group and M-HPCS 3 / HA-PEG 7 +Mg 2+ The wound healing rates in the hydrogel + NIR group were the highest, at 62.25% and 63.75%, respectively. It can be seen that from the 7th day to the 14th day, the healing rate of the blank group increased faster, which may be due to the M-HPCS 7 / HA-PEG 3 and M-HPCS 3 / HA-PEG 7 +Mg 2+ The hydrogel has anti-inflammatory and fibroblast over-proliferation effects. The hydrogel can make the wound surface normally enter the proliferation stage from the inflammatory stage. Therefore, the healing rate of the hydrogel group was higher on the 7th day. After that, in order to avoid the formation of scar tissue, the hydrogel will inhibit the over-proliferation of fibroblasts, resulting in a slight decrease in the proliferation rate of fibroblasts in the wound surface of the hydrogel group. On the 21st day, except for the control group, the healing rate of the wound surface of each group was greater than 90%, and on the 28th day, the M-HPCS 7 / HA-PEG 3 Hydrogel+NIR and M-HPCS 3 / HA-PEG 7 +Mg 2+ The wound healing rate of the hydrogel + NIR group has basically reached 100%, achieving complete healing, while some wounds in the control group and the positive group have not yet completely healed. The results show that hydrogel can effectively promote wound healing, and photothermal therapy can effectively promote wound healing on the basis of using functional dressings.

[0191] 15. In vivo photothermal conversion analysis

[0192] In the in vivo wound healing experiment, a combination of hydrogel and photothermal therapy was used, that is, M-HPCS 7 / HA-PEG 3 Hydrogel+NIR, M-HPCS 3 / HA-PEG 7 +Mg 2+ Hydrogel + NIR two groups of photothermal therapy. First, in the preliminary experiment, the optimal power used in photothermal therapy was studied. 7 / HA-PEG 3 Hydrogel, M-HPCS 3 / HA-PEG 7 +Mg 2+ The hydrogel was applied to the wound surface and different optical densities were used, 1.0 W / cm 2 , 1.25W / cm 2, 1.5W / cm 2 The hydrogel was irradiated with 808nm near-infrared light for 5 minutes, and the temperature changes at the wound site were recorded with an infrared camera. Fig.21 As shown, at an optical density of 1 W / cm 2 808nm near-infrared light irradiation for 5min, M-HPCS 7 / HA-PEG 3 Hydrogel group and M-HPCS 3 / HA-PEG 7 +Mg 2+ The highest temperature of the hydrogel group can reach about 42°C; at an optical density of 1.25W / cm 2 Under 808nm near-infrared light irradiation, M-HPCS 7 / HA-PEG 3 Hydrogel group and M-HPCS 3 / HA-PEG 7 +Mg 2+ The highest temperature of the hydrogel group could reach about 43°C within 5 minutes; 2 Under 808nm near-infrared light irradiation, M-HPCS 7 / HA-PEG 3 Hydrogel group and M-HPCS 3 / HA-PEG 7 +Mg 2+ The temperature of the hydrogel group can reach about 45°C after 3 minutes of irradiation, and the highest temperature can reach about 50°C within 5 minutes. The results show that the optical density is 1.5W / cm 2 M-HPCS 7 / HA-PEG 3 Hydrogel group and M-HPCS 3 / HA-PEG 7 +Mg 2+ The temperature that the hydrogel can reach is suitable for wound healing. Therefore, in the subsequent treatment process, M-HPCS 7 / HA-PEG 3 Hydrogel+NIR, M-HPCS 3 / HA-PEG 7 +Mg 2+ The light density was 1.5 W / cm2 for each dressing change in the hydrogel + NIR group. 2 The 808nm near-infrared light was irradiated for 5 minutes until the treatment was completed.

[0193] 16. Histopathological analysis of wound repair

[0194] (1) Analysis of HE staining results

[0195] like Fig. 22 As shown in the figure, on the third day of wound treatment, the skin epidermis in each group was damaged, the structure was blurred, the collagen fibers in the dermis were severely degenerated and arranged in disorder, there were a few remaining hair follicles, and the sebaceous glands and other appendages had been destroyed, which was consistent with the pathological organization of II degree burns. There was obvious congestion. On the 7th day, the wound surface was infiltrated with inflammatory cells, vacuoles appeared in the dermis, and the tissue was completely necrotic. The inflammatory cells in the dermis in the control group and the positive control group were significantly less than those in the experimental group. The collagen fibers in the dermis in each group were thick and arranged in disorder; on the 14th day, no epidermal formation was observed in the control group, a large number of inflammatory cells were present in the dermis, and the collagen fibers were still extremely disordered. Re-epithelialization had not begun in the positive control group, and a large number of inflammatory cells infiltrated the dermis. In the experimental group, a thinner epidermis had been formed, a large number of capillaries and fibroblasts were generated in the dermis, and there was still inflammatory cell infiltration, but it was significantly reduced. On the 21st day, the epidermis in the control group did not reach complete re-epithelialization, the epidermis continued to thicken, fibrosis was visible in the dermis, and no obvious skin hair follicles and sebaceous glands and other appendages were seen. In the experimental group, most of the scabs on the wound surface fell off, epithelial cells regenerated, the epidermis thickened, and the papillary layer was obviously formed. The structure was almost close to that of normal skin, and the boundary between the epidermis and the dermis was also relatively obvious. The collagen fibers in the dermis of the experimental group and the positive control group were arranged neatly and basket-shaped, and there was obvious new granulation tissue, increased fibroblasts and new blood vessels, and hair follicles and sebaceous glands were visible in some areas. On the 28th day, there was still congestion in the control group, and the wound in the experimental group was completely healed, the epidermis was thinned, the differentiation was relatively complete, the structure was good, the dermis had a uniform distribution of skin appendages, and the collagen fibers were arranged neatly, which was the same as the normal skin tissue structure.

[0196] (2) Analysis of Masson staining results

[0197] like Fig.23As shown in the figure, the same as the results of HE staining, on the 3rd day, the epidermis of the wound skin in each group was damaged, the structure was blurred, the collagen fibers in the dermis were severely degenerated and arranged in disorder, there were a few remaining hair follicles, and the sebaceous glands and other appendages were destroyed, which was consistent with the pathological organization of second-degree burns. On the 7th day, the wound tissue was completely necrotic, with inflammatory cell infiltration, vacuoles in the dermis, and the collagen fibers in the dermis of each group were thick and arranged in disorder; on the 14th day, the necrotic tissue in the control group was still not cleaned up and had not entered the proliferation stage, while there were a large number of inflammatory cells in the dermis of the hydrogel group, and the collagen fibers were still arranged in disorder, but a large number of capillaries and fibroblasts were generated in the dermis, and new collagen fibers were generated. On the 21st day, the epidermis in the control group did not achieve complete re-epithelialization, the epidermis continued to thicken, fibrosis was seen in the dermis, and no obvious skin hair follicles and sebaceous glands and other appendages were seen. Most of the scabs on the wound surface of the hydrogel group fell off, and it can be seen that the epidermal structure is basically intact, the papillary layer is clearly formed, and the boundary between the epidermis and the dermis is also relatively obvious. The collagen fibers in the dermis of the experimental group and the positive control group are arranged neatly and basket-shaped. The dermis has been completely repaired, and hair follicles and sebaceous gland structures can be seen in some areas. On the 28th day, there was still congestion in the control group, and some wounds had not been repaired and were still in the proliferation stage; the wounds in the hydrogel group were completely healed, the epidermal differentiation was relatively complete, the structure was good, the dermis had a uniform distribution of skin appendages, and the collagen fibers were neatly arranged, which was the same as the normal skin tissue structure.

[0198] (3) Immunofluorescence staining analysis

[0199] like Fig.24 As shown, the wounds treated with saline only (control group) had a higher iNOS (red) fluorescence level, indicating that the wounds in the control group were still in a severe inflammatory stage, while the red fluorescence signals in the wounds treated with other groups were reduced compared with the control group, indicating that the positive control group, M-HPCS 7 / HA-PEG 3 、M-HPCS 3 / HA-PEG 7 +Mg 2+ The inflammatory response at the wound site in the hydrogel and NIR groups was at normal levels, indicating that the two hydrogels can synergistically promote the polarization of M1 macrophages to M2 macrophages to regulate inflammation and promote wound repair.

[0200] like Fig.25 As shown, M-HPCS can be found 7 / HA-PEG 3 Hydrogel, M-HPCS 3 / HA-PEG 7 +Mg 2+ The green fluorescence signals of the two hydrogel groups were stronger than those of the control group, and after combined photothermal therapy, M-HPCS7 / HA-PEG 3 Hydrogel+NIR, M-HPCS 3 / HA-PEG 7 +Mg 2+ There were more green fluorescence signals in the wound sites treated with hydrogel + NIR, indicating that near-infrared light irradiation can promote the transformation of macrophages to M2 type and the wound has entered the proliferation stage normally. 7 / HA-PEG 3 Hydrogel, M-HPCS 3 / HA-PEG 7 +Mg 2+ Hydrogel treatment enabled diabetic skin wounds to successfully enter the proliferation stage from the inflammatory stage. In contrast, the CD206 fluorescence signal in the wound tissue after treatment in the control group was weak, indicating that the number of M2 macrophages in the wound was small and the wound was still in a prolonged inflammatory stage. The results once again confirmed that M-HPCS 7 / HA-PEG 3 Hydrogel, M-HPCS 3 / HA-PEG 7 +Mg 2+ The hydrogel can promote the transformation of macrophages to the M2 type and effectively regulate the inflammatory response in diabetic skin wounds, thereby promoting the formation of granulation tissue in the wounds and accelerating the healing of diabetic skin wounds. In addition, iNOS and CD206 immunofluorescence staining showed that the therapeutic effect of the hydrogel can be enhanced after combined photothermal therapy.

[0201] CD31 is a transmembrane protein expressed in the early stage of angiogenesis, and α-SMA is a cytoplasmic protein expressed in the late stage of angiogenesis. It marks the maturation of vascular smooth muscle cells and is associated with tissue fibrosis and wound contraction. Fig.26 and 27 It was observed that on day 7, M-HPCS 7 / HA-PEG 3 Hydrogel and M-HPCS 3 / HA-PEG 7 +Mg 2+ The fluorescence signals of CD31 and α-SMA in the hydrogel were strong, and in the group treated with photothermal therapy, the fluorescence signal levels of CD31 and α-SMA were higher. The results showed that M-HPCS 7 / HA-PEG 3 Hydrogel and M-HPCS 3 / HA-PEG 7 +Mg 2+Hydrogels can promote angiogenesis during skin wound healing, and can further promote angiogenesis through photothermal therapy. Both hydrogels can promote the healing of diabetic wounds by regulating the polarization of macrophages and promoting the formation of new blood vessels. Photothermal therapy of the wound will further enhance the therapeutic effect of the hydrogel.

[0202] Finally, although this specification is described according to implementation methods, not every implementation method contains only one independent technical solution. This narrative method of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation methods that can be understood by those skilled in the art.

Claims

1. A melanin-hydroxypropyl chitosan / hyaluronic acid-bisamino polyethylene glycol composite hydrogel, characterized in that: The composite hydrogel is prepared by mixing hydroxypropyl chitosan grafted with melanin and hyaluronic acid-bisamino polyethylene glycol.

2. The method for preparing the composite hydrogel according to claim 1, characterized in that: The following steps are involved: (1) Hydrophilic modification of chitosan was performed through etherification reaction to obtain hydroxypropyl chitosan, and then melanin was grafted onto HPCS through amide reaction to prepare M-HPCS; HA-PEG was prepared through amide reaction; (2) preparing an M-HPCS solution and a HA-PEG solution, and then mixing the M-HPCS solution and the HA-PEG solution evenly and placing the mixture in a water bath to obtain a composite hydrogel.

3. The preparation method according to claim 2, characterized in that: In the step (2), the prepared M-HPCS and HA-PEG are dissolved in deionized water to prepare solutions with concentrations of 7% and 4% (w / v), respectively; the volume ratio of the M-HPCS solution to the HA-PEG solution is 3-7:7-3.

4. The preparation method according to claim 3, characterized in that: The volume ratio of the M-HPCS solution to the HA-PEG solution is 7:3; the water bath temperature is 45°C-60°C.

5. A M-HPCS / HA-PEG / soluble metal ion composite hydrogel, characterized in that: The composite hydrogel is prepared by adding a soluble metal ion solution to the hydroxypropyl chitosan solution grafted with melanin as claimed in claim 1 and the hyaluronic acid-bisamino polyethylene glycol solution while stirring and mixing them.

6. The method for preparing the M-HPCS / HA-PEG / soluble metal ion composite hydrogel according to claim 5, characterized in that: The following steps are involved: (1) Hydrophilic modification of chitosan was performed by etherification reaction to obtain hydroxypropyl chitosan, and then melanin was grafted onto HPCS by amide reaction to prepare M-HPCS; HA-PEG was prepared by amide reaction; (2) preparing an M-HPCS solution and a HA-PEG solution, then mixing the M-HPCS solution and the HA-PEG solution evenly, adding a soluble metal ion solution dropwise while mixing, and placing the mixture in a water bath for a certain period of time to obtain the composite hydrogel.

7. The preparation method according to claim 6, characterized in that: In the step (2), the prepared M-HPCS and HA-PEG are dissolved in deionized water to prepare solutions with concentrations of 7% and 4% (w / v), respectively; the volume ratio of the M-HPCS solution: HA-PEG solution is 3-7:7-3.

8. The preparation method according to claim 7, characterized in that: The ratio of the M-HPCS solution to the HA-PEG solution was 3:7 (v / v); the concentration of the added soluble metal ion solution was 4% (w / v), and the added volume percentage was 5%.

9. Use of the M-HPCS / HA-PEG composite hydrogel according to claim 1 in the preparation of products having antioxidant effects, promoting cell growth, promoting new blood vessel formation, products having photothermal properties, and products promoting skin wound healing.

10. Use of the M-HPCS / HA-PEG / soluble metal ion composite hydrogel according to claim 1 in the preparation of products for anti-oxidation, cell growth promotion, angiogenesis promotion, photothermal performance products, and skin wound healing promotion products.

Citation Information

Patent Citations

  • Nano material as well as preparation method and application thereof

    CN114681627A

  • Injectable photo-thermal hydrogel based on ink melanin as well as preparation method and application of injectable photo-thermal hydrogel

    CN116919886A